Humic substances benefiting the development of Arachis pintoi cv. Amarillo MG 100 (forage peanut) cultivated on degraded soil - Oliveira, D. M.; Thiengo, C. C.; Bolzan, Lenita J.; Mendoça, E. S.; Burak, D. L. (Cuban Journal of Agricultural Science, 2021)
Humic substances are increasingly being used as biostimulants and may even benefit the development of forage peanut (Arachis pintoi cv. Amarillo MG 100), a promising species for the recovery of degraded pastures. The study aimed to evaluate different concentrations of humic substances extracted from vermicompost from cattle manure on growth and nutrient content in forage peanut plants inoculated with Bradyrhizobium spp. The experiment was carried out in a greenhouse, in a randomized block design, with five concentrations of humic substance and five replications. The shoot dry matter, root dry matter, the number of nodules, the content of macronutrients in the shoot, total chlorophyll content, chlorophyll a/b ratio, and quantum efficiency of the photosystem II were evaluated. The addition of humic substances increased the yield and nutrient accumulation of the forage peanut plants. The shoot dry matter responded in a quadratic manner to the addition of humic substances. The concentration of 40 mg L-1 of C increased 45.85% of the number of nodules compared to the control. There were improvements in efficiency of the photosystem II and the accumulation of nitrogen, potassium, calcium and magnesium by up to 12 % (37.1 to 41.5 mg pot-1), 8.6 % (35.3 to 38.3 mg pot-1), 13.5 % (21.8 to 24.7 mg pot-1) and 7.5 % (9.8 to 10.53 mg pot-1), respectively, in the shoot with the humic substances application, except for the phosphorus accumulation. Keywords: biostimulants, nodulation, soil of low fertility, photosystem II, Bradyrhizobium